Interaction of N‐methylformanilide with high‐performance polyimide fibre and its effect on dyeing. (30th March 2022) - Shao, Dongyan; Du, Jinmei; Xu, Changhai; Wang, Hongbo
Abstract: High‐performance polyimide fibre is well known for its outstanding thermal stability, fire resistance and chemical stability, and it has great potential for use in fire‐protective textiles. One major drawback of polyimide fibre is that it is difficult to dye under regular conditions. In this work, it was found that polyimide fibre could be dyed with disperse dyes with the assistance of N ‐methylformanilide. Thus, it was proposed that there might exist an interaction between polyimide fibre and N ‐methylformanilide that plays an important role in dyeing. Experimental results showed that N ‐methylformanilide penetrated into polyimide fibre, resulting in a slight swell in diameter and decrease in the breaking strength of polyimide fibre. X‐ray diffractometric data showed no apparent solvent‐introduced increase on the crystallinity of polyimide fibres but an orderly change on the interplanar spacing. When N ‐methylformanilide was removed from polyimide fibre by thermal treatment, the diameter, breaking strength and interplanar spacing of the polyimide fibres were all recovered to some extent. This indicated that the interactions between polyimide macromolecular chains were broken because of the penetration of N ‐methylformanilide, and new interactions occurred between polyimide macromolecular chains and N ‐methylformanilide that played a role in lubricating dye molecules to diffuse into polyimide fibres.